Metabolic and histological implications of intrahepatic triglyceride content in nonalcoholic fatty liver disease. Issue 4 (25th February 2017) - Bril, Fernando; Barb, Diana; Portillo‐Sanchez, Paola; Biernacki, Diane; Lomonaco, Romina; Suman, Amitabh; Weber, Michelle H.; Budd, Jeffrey T.; Lupi, Maria E.; Cusi, Kenneth
Abstract : The cut‐off point of intrahepatic triglyceride (IHTG) content to define nonalcoholic fatty liver disease (NAFLD) by proton magnetic resonance spectroscopy ( 1 H‐MRS) was established based on the 95th percentile in a group of healthy individuals (i.e., ≥5.56%). Whether this threshold correlates with metabolic and histological changes and whether a further accumulation of IHTG is associated with worsening of these parameters has not been properly assessed in a large cohort of patients. In this cross‐sectional study, 352 subjects were carefully characterized with the following studies: liver 1 H‐MRS; euglycemic insulin clamp with measurement of glucose turnover; oral glucose tolerance test; and a liver biopsy. Hepatic insulin sensitivity (suppression of endogenous glucose production by insulin) was affected early on after IHTG content was ∼1.5% and remained uniformly impaired (∼40%‐45%), regardless of further IHTG accumulation. Skeletal muscle insulin sensitivity showed a gradual impairment at low degrees of IHTG accumulation, but remained unchanged after IHTG content reached the ∼6 ± 2% threshold. A similar pattern was observed for metabolic changes typically associated with NAFLD, such as hypertriglyceridemia and low high‐density lipoprotein cholesterol (HDL‐C). In contrast, adipose tissue insulin sensitivity (suppression of free fatty acids by insulin) showed a continuous worsening across the spectrum of IHTG accumulation in NAFLD (r = –0.38; P < 0.001). Histological severity of liver disease (inflammation, ballooning, and fibrosis) was not associated with the amount of IHTG content. Conclusion : IHTG accumulation is strongly associated with adipose tissue insulin resistance (IR), supporting the current theory of lipotoxicity as a driver of IHTG accumulation. Once IHTG accumulation reaches ∼6 ± 2%, skeletal muscle IR, hypertriglyceridemia, and low HDL‐C become fully established. Histological activity appears to have an early threshold and is not significantly influenced by increasing amounts of IHTG accumulation. (Hepatology 2017;65:1132‐1144).